Determinants of Reputation, Experience and Communication on Employer Branding - Ricardo, Ricardo (Dinasti Research, 2022)
The Literature Review Article on Determinants of Reputation, Experience and Communication on Employer Branding is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Reputation affects Employer Branding; 2) Experience has an effect on Employer Branding; and 3) Communication has an effect on Employer Branding. Apart from these 3 exogenous variables that affect the endogenous variable Employer Branding, there are still many other factors including Talent, Recruitment, Value Proposition variables.